İyimserlik (Yaşam Yönelimi) ile Yaşam Doyumu Arasındaki İlişkide Akademik Başarının Aracılık Rolü - Erdogdu, Mustafa Yuksel; Erdogdu, Mustafa Yüksel (Turkish Education Assoc, 2021)
This article investigates whether academic achievement plays a mediating role in the relationship between optimism and life satisfaction. The study was designed using the correlational survey method. Four hundered and thirty-five (215 females and 220 males) high school students were chosed as the particpants of the study. The mean age of the students was 16.21. The Optimism (Life Orientation) Scale and the Life Satisfaction Scale were used in the study, and the academic achievement grades of the students were obtained from the report card notes from the previous year. To test the mediating effect of the applied model, the regression-based bootstrapping method and the Pearson moment-product correlation coefficient were used. Results showed there was a relationship between optimism, academic achievement, and life satisfaction. Furthermore, it was found that academic achievement played a partial mediating role in the relationship between optimism and life satisfaction. It was also observed that as students' optimistic thoughts increased, their academic achievement also increased, and consequently, they became more satisfied with life. The findings were discussed in general terms, and recommendations were made accordingly.

Bu araştırmanın amacı iyimserlik ile yaşam doyumu arasındaki ilişkide akademik başarının aracı rolüne sahip olup olmadığını incelemektir. Araştırma, ilişkisel tarama modelinde düzenlenmiştir. Araştırma, 215’i kadın, 220’si erkek olmak üzere toplam 435 lise öğrencisi üzerinde yürütülmüştür. Öğrencilerin yaş ortalaması 16.21 olarak hesaplanmıştır. Araştırmada İyimserlik (Yaşam Yönelimi) Ölçeği ile Yaşam Doyumu Ölçeği kullanılmış, öğrencilerin akademik başarı notları ise bir önceki yıl karne notlarından elde edilmiştir. Araştırmada, Pearson momentler çarpımı koreleasyon katsayısı ile uygulanan modelin aracılık etkisini test etmek için regresyon temelli bootstrapping yöntemi kullanılmıştır. Elde edilen sonuçlara göre iyimserlik, akademik başarı ve yaşam doyumu arasında ilişkiler bulunmaktadır. Ayrıca iyimserlik ile yaşam doyumu arasında akademik başarının kısmi aracılık rolünde olduğu görülmektedir. Sonuç olarak öğrencilerim iyimserlik düşünceleri arttıkça akademik başarılarının da yükseldiği bunun sonucu olarak da yaşamdan daha fazla doyum aldıkları görülmektedir. Bulgular genel hatlarıyla tartışılarak yorumlanmış ve önerilerde bulunulmuştur.
The Mediating Role of Academic Achievement in The Relationship Between Optimism (Life Orientation) and Life Satisfaction
Keywords: Optimism; Academic Achievement; Life Satisfaction; İyimserlik; Akademik Başarı; Yaşam Doyumu